Effectiveness of Investigations into Aggravated Theft Crimes - Diki Zulnaedi; Bambang Tri Bawono (Jurnal Hukum Khaira Ummah, 2025)
This study aims to determine and analyze the implementation of investigations into the crime of aggravated theft at the Bintan Resort Police and the effectiveness of the implementation of investigations into the crime of aggravated theft at the Bintan Resort Police. The approach method in this study is sociological juridical, the research specification is analytical descriptive. The data used are primary data and secondary data and the data collection method is field study and literature study, while the data analysis method uses qualitative analysis. The theory used in this study is the theory of legal effectiveness and legal certainty. The results of the study indicate that the implementation of investigations into the crime of aggravated theft at the Bintan Resort Police has been carried out in accordance with the provisions of the Criminal Procedure Code and the Regulation of the Chief of Police Number 6 of 2019 concerning Criminal Investigations so that it has fulfilled the principle of legal certainty. The implementation of investigations into the crime of aggravated theft at the Bintan Resort Police has also been effective, this is reflected in the majority of police reports that can be handled well until the stage of transferring case files to the prosecutor's office. Despite several obstacles, overall the investigation process continued to run well and was able to support law enforcement in a professional and proportional manner.